A stretchable organic electrochemical transistor and a method for preparing the same
By adopting a multi-layer porous semiconductor layer structure in organic electrochemical transistors, the problem of insufficient contact and penetration of liquid electrolyte and semiconductor layer is solved, the output current and mechanical flexibility are improved, and efficient electrochemical performance is achieved.
Patent Information
- Application Number
- CN202210804662.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-08
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-07-08
AI Technical Summary
In the organic electrochemical transistor, the output current is not ideal due to insufficient contact and penetration of the liquid electrolyte with the semiconductor layer.
Using a multi-layer porous semiconductor layer structure, the porous semiconductor layer is prepared by spin coating and photolithography technology, increasing the contact area between the electrolyte and the semiconductor layer, and balancing electron transport and ion permeation/transmission.
Improves the output drain current and mechanical flexibility of the device, enhances the overall performance of the device, achieves low voltage operation and reduces power consumption losses.
Smart Images

Figure CN115172589B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of flexible organic electrochemical transistors or flexible electronics, and in particular to a stretchable organic electrochemical transistor and a preparation method thereof. Background Art
[0002] Traditional transistor devices have the advantages of signal amplification, easy integration, fast response speed, and high accuracy. They are one of the basic components of modern electronics and have been widely used in fields such as integrated circuits. On the basis of traditional transistor devices, organic electrochemical transistor (OECT) devices also have the characteristics of high transconductance, low voltage, large capacitance, and compatibility with water environment. Its most significant advantage can be briefly described as the ability to generate a large current density at a gate drive voltage of less than 1V and achieve a high transconductance value of up to the mS level. It has broad prospects in the fields of intelligent medical diagnosis, biological signal perception, neuromorphic computing, and digital logic circuits.
[0003] Organic electrochemical transistors rely on the transport of ions and charges (electrons / holes) through the gate voltage (V G ) effectively controls the injection of electrolyte ions into the semiconductor channel to electrochemically dope the semiconductor to adjust the conductivity. The transport of ions depends on the contact between the electrolyte and the semiconductor layer, and the penetration is carried out under the regulation of voltage. Charge transport in OECT runs through the entire thickness of the semiconductor film to form a three-dimensional transport channel. According to the Bernards model, the organic electrochemical transistor device can be simply understood as a combination of an ionic circuit and an electronic circuit. Among them, the ionic circuit is composed of a resistor describing the flow of ions in the electrolyte ions and a capacitor describing the storage of ions at the gate-electrolyte interface and the channel volume in series along the gate-electrolyte-channel direction. The proportional size of the gate voltage drop applied to the channel is controlled by the properties and geometry of the gate electrode. Using a non-polarized gate electrode, such as Ag / AgCl, the voltage drop at the gate-electrolyte interface can be ignored. The electronic circuit is equivalent to a variable resistor affected by the ionic circuit along the source-channel-drain direction. Summary of the invention
[0004] The purpose of the present invention is to provide a stretchable organic electrochemical transistor based on a multi-layer porous semiconductor layer and a preparation method thereof, aiming to solve the shortcomings of the electrochemical transistor in which the output current is not ideal due to insufficient contact and penetration of the liquid electrolyte with the semiconductor layer, while utilizing the liquid electrolyte to penetrate into the multi-layer porous organic semiconductor layer to balance the electron transmission and ion penetration / transmission in the semiconductor layer, thereby improving the overall performance of the device.
[0005] The technical solution adopted by the present invention is as follows:
[0006] A stretchable organic electrochemical transistor comprises, from bottom to top, a flexible substrate layer, an electrode layer, a multi-layer porous semiconductor layer, an electrolyte layer and a gate electrode; the electrode layer comprises a source electrode and a drain electrode; the multi-layer porous semiconductor layer is a thin film of a multi-layer porous solid semiconductor.
[0007] Preferably, the material of the flexible substrate layer is at least one of SEBS, PDMS and PU.
[0008] Preferably, the electrode layer is made of gold, and the thickness of the electrode layer is in the range of 80 to 150 nm.
[0009] Preferably, the material of the multilayer porous semiconductor layer is prepared by mixing a polymer, an organic semiconductor and a crosslinking agent; the polymer is one of polystyrene-b-polyethylene oxide-b-polystyrene, polystyrene-b-polymethyl methacrylate-b-polystyrene, polystyrene-b-polyethyl acrylate-b-polystyrene, poly N-isopropylacrylamide-b-polyethylene oxide-b-poly N-isopropylacrylamide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and poly (vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene); the organic semiconductor is one of P3HT, Pg2T-T, DPP-DTT; the crosslinking agent is at least one of a bis(nitrogen heterocyclic) crosslinking agent and a bis(azide) crosslinking agent, and the film thickness ranges from 200 to 300 nm.
[0010] Preferably, the material of the electrolyte layer is a salt aqueous solution or an ionic liquid, the salt aqueous solution is one of NaCl, KCl and PBS, and the ionic liquid is one of [EMIM][TFSI], [EMIM][FSI], [EMIM][DCA], [BMIM][PF6] and [EMIM][BF4].
[0011] Preferably, the preparation process comprises the following steps:
[0012] Step 1: Clean the transparent glass substrate, blow dry it with nitrogen or heat dry it in a constant temperature oven for more than 6 hours after cleaning;
[0013] Step 2: Pour SEBS, PDMS or PU onto a glass substrate coated with detergent, and after the solution is spread flat, place it in a vacuum drying oven to dry it to obtain a flexible substrate layer. After drying, peel the flexible substrate layer from the glass substrate with a blade;
[0014] Step 3: Evaporating a gold electrode (80-150 nm) on the flexible substrate layer;
[0015] Step 4: Clean the microscope slide, blow dry with nitrogen or heat dry in a constant temperature oven for more than 6 hours after cleaning;
[0016] Step 5: Spin-coat the prepared PVA solution onto a microscope slide, and dry the spin-coated substrate to obtain a PVA sacrificial layer;
[0017] Step 6: Spin-coat the prepared mixed chloroform solution of polymer, organic semiconductor and cross-linking agent onto the PVA sacrificial layer, and then place it under 365nm ultraviolet light for photo-cross-linking and curing to form a cross-linked semiconductor layer;
[0018] Step 7: Soak the cross-linked organic semiconductor layer / PVA / substrate after photo-cross-linking and curing in chloroform for 10 seconds to remove the uncross-linked part in the polymer to form pores, blow off the surface solvent with nitrogen gas, and then dry;
[0019] Step 8: placing the cross-linked organic semiconductor layer / PVA / substrate in a culture dish filled with 40° C. deionized water, dissolving the PVA sacrificial layer in the deionized water to obtain a single porous semiconductor layer, transferring the first porous semiconductor layer to the flexible substrate, and drying it with nitrogen, repeatedly transferring the second porous semiconductor layer to the first porous semiconductor layer, and drying it with nitrogen, and repeatedly transferring the third porous semiconductor layer to the second porous semiconductor layer, and drying it with nitrogen;
[0020] Step 9: Drip the electrolyte onto the semiconductor channel.
[0021] Preferably, in step 2, the drying temperature is 30° C. and the drying time is at least 24 hours.
[0022] Preferably, in step 5, the drying temperature is 110° C. and the drying time is at least 1 minute.
[0023] Preferably, the drying method adopts at least one of constant temperature hot plate heating, oven heating and hot air heating.
[0024] The beneficial effects of the present invention are as follows:
[0025] 1. A porous antireflection film is prepared by spin coating a mixed solution of a polymer, an organic semiconductor and a cross-linking agent. The porous semiconductor layer can be easily prepared by adjusting the proportion of the organic semiconductor to control the morphology of the porous film without a high humidity environment, effectively increasing the contact area between the semiconductor layer and the electrolyte layer, which is more conducive to the injection of electrolyte ions into the channel, enhancing the ion-electron capacitive coupling in the channel, achieving low-voltage operation, and reducing device power consumption losses.
[0026] 2. By simply stacking multiple layers of porous semiconductor films, the number of reaction sites for electrochemical doping in the semiconductor can be effectively increased, the electrochemical doping of electrolyte ions and semiconductor layers can be strengthened, the output drain current of the device can be increased, and the regulation of the output by the input gate voltage can be enhanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the proportional relationship of the various components in the drawings of this specification does not represent the proportional relationship in actual material selection and design, which is only a schematic diagram of the structure or position, wherein:
[0028] Figure 1 It is a schematic diagram of the structure of the present invention;
[0029] Figure 2 is a schematic structural diagram of the porous semiconductor layer 11 of the present invention;
[0030] Figure 3 is a schematic structural diagram of a dense semiconductor film 22 of the present invention;
[0031] Description of the reference numerals in the accompanying drawings:
[0032] 1-flexible substrate layer; 2-source electrode; 3-drain electrode; 4-gate electrode; 5-multi-layer porous semiconductor layer; 6-electrolyte layer; 11-porous semiconductor film; 22-dense semiconductor film. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.
[0034] Combine the following Figures 1 to 3 , the present invention is described in detail.
[0035] A stretchable organic electrochemical transistor comprises, from bottom to top, a flexible substrate layer, an electrode layer, a multi-layer porous semiconductor layer, an electrolyte layer and a gate electrode; the electrode layer comprises a source electrode and a drain electrode; the multi-layer porous semiconductor layer is a thin film of a multi-layer porous solid semiconductor.
[0036] Embodiment 1 (control group):
[0037] 1. Clean the transparent glass substrate with a surface roughness less than 1nm, and then heat dry it in a constant temperature oven for more than 6 hours;
[0038] 2. Apply a layer of detergent on the glass substrate, pour the PU on the glass substrate coated with detergent, vibrate slightly, spread the solution flat, and place it in a vacuum drying oven for drying (30°C, 24h). After drying, use a blade to carefully peel the flexible substrate from the glass substrate;
[0039] 3. Vacuum degree is 1×10 -4Under Pa conditions, gold electrodes (80 nm) were evaporated on the PU substrate;
[0040] 4. Clean the microscope slides with a surface roughness of less than 1 nm and heat dry them in a constant temperature oven for more than 6 hours after cleaning;
[0041] 5. Spin-coat the prepared PVA solution onto a microscope slide (3000 rpm, 60 s), and dry the slide after spin coating (110°C, 1 min) to obtain a PVA sacrificial layer;
[0042] 6. Spin-coat the prepared P3HT mixed solution (P3HT:SEBS=2:1) onto the PVA sacrificial layer (5000 rpm, 10 s);
[0043] 7. Observe the P3HT film under SEM and find that the surface of the P3HT film is flat and dense. Figure 3 The dense semiconductor film 22 is shown;
[0044] 8. Place the spin-coated glass slide in a culture dish filled with deionized water, and place the culture dish on a hot plate (40°C) to dissolve the PVA sacrificial layer in the deionized water to obtain a semiconductor active layer. Transfer a layer of the semiconductor active layer to the flexible substrate and blow dry with nitrogen;
[0045] 9. Drip electrolyte on the semiconductor channel and insert Ag / AgCl gate electrode;
[0046] 10. Under test conditions: leakage voltage (V D )=-0.5V, gate voltage (V G ) scanning interval is 0.1~-1V, [EMIM][TFSI] ionic liquid is dripped on the semiconductor channel, and the on-off ratio (I on / I off ) = 2 × 10 3 , transconductance (g m )=0.52mS. If the device is not packaged, it is not easy to store for a long time and direct stretching will damage the device.
[0047] Embodiment 2:
[0048] 1. Clean the transparent glass substrate with a surface roughness less than 1nm, and then heat dry it in a constant temperature oven for more than 6 hours;
[0049] 2. Apply a layer of detergent on the glass substrate, pour the PU on the glass substrate coated with detergent, vibrate slightly, spread the solution flat, and place it in a vacuum drying oven for drying (30°C, 24h). After drying, use a blade to carefully peel the flexible substrate from the glass substrate;
[0050] 3. Vacuum degree is 1×10-4 Under Pa conditions, gold electrodes (80 nm) were evaporated on the PU substrate;
[0051] 4. Clean the microscope slides with a surface roughness of less than 1 nm and heat dry them in a constant temperature oven for more than 6 hours after cleaning;
[0052] 5. Spin-coat the prepared PVA solution onto a microscope slide (3000 rpm, 60 s), and dry the slide after spin coating (110°C, 1 min) to obtain a PVA sacrificial layer;
[0053] 6. A mixed chloroform solution of the prepared PS-PEO-PS triblock polymer, P3HT organic semiconductor and DA crosslinker (mass ratio PS-PEO-PS: P3HT: DA: chloroform = 3:15:1:200, 5000 rpm, 60 s, 80 nm) was spin-coated onto the PVA sacrificial layer, and then placed under 365 nm ultraviolet light for photolithography to form a crosslinked organic semiconductor layer;
[0054] 7. Observe the P3HT film under SEM and find that the surface of the P3HT film has evenly distributed pores. Figure 2 The porous semiconductor film 11 is shown;
[0055] 8. Place the spin-coated glass slide in a culture dish filled with deionized water, and place the culture dish on a hot plate (40°C) to dissolve the PVA sacrificial layer in the deionized water to obtain a semiconductor active layer. Transfer a layer of the semiconductor active layer to the flexible substrate and blow dry with nitrogen;
[0056] 9. Drip electrolyte on the semiconductor channel and insert Ag / AgCl gate electrode;
[0057] 10. Under test conditions: leakage voltage (V D )=-0.5V, gate voltage (V G ) scanning interval is 0.1~-1V, [EMIM][TFSI] ionic liquid is dripped on the semiconductor channel, and the on-off ratio (I on / I off )=2.4×10 3 , transconductance (g m )=0.62mS. If the device is not packaged, it is not easy to store for a long time and direct stretching will damage the device.
[0058] Embodiment 3:
[0059] 1. Clean the transparent glass substrate with a surface roughness less than 1nm, and then heat dry it in a constant temperature oven for more than 6 hours;
[0060] 2. Apply a layer of detergent on the glass substrate, pour the PU on the glass substrate coated with detergent, vibrate slightly, spread the solution flat, and place it in a vacuum drying oven for drying (30°C, 24h). After drying, use a blade to carefully peel the flexible substrate from the glass substrate;
[0061] 3. Vacuum degree is 1×10 -4 Under Pa conditions, gold electrodes (80 nm) were evaporated on the PU substrate;
[0062] 4. Clean the microscope slides with a surface roughness of less than 1 nm and heat dry them in a constant temperature oven for more than 6 hours after cleaning;
[0063] 5. Spin-coat the prepared PVA solution onto a microscope slide (3000 rpm, 60 s), and dry the slide after spin coating (110°C, 1 min) to obtain a PVA sacrificial layer;
[0064] 6. A mixed chloroform solution of the prepared PS-PEO-PS triblock polymer, P3HT organic semiconductor and DA crosslinker (mass ratio PS-PEO-PS: P3HT: DA: chloroform = 3:20:1:200, 5000 rpm, 60 s, 80 nm) was spin-coated onto the PVA sacrificial layer, and then placed under 365 nm ultraviolet light for photolithography to form a crosslinked organic semiconductor layer;
[0065] 7. Observe the P3HT film under SEM and find that the surface of the P3HT film has evenly distributed pores. Figure 2 The porous semiconductor film 11 is shown;
[0066] 8. Place the spin-coated glass slide in a culture dish filled with deionized water, and place the culture dish on a hot plate (40°C) to dissolve the PVA sacrificial layer in the deionized water to obtain a semiconductor active layer. Transfer a layer of the semiconductor active layer to the flexible substrate and blow dry with nitrogen;
[0067] 9. Under test conditions: leakage voltage (V D )=-0.5V, gate voltage (V G ) scanning interval is 0.1~-1V, [EMIM][TFSI] ionic liquid is dripped on the semiconductor channel, and the on-off ratio (I on / I off )=2.5×10 3 , transconductance (g m )=0.65mS. If the device is not packaged, it is not easy to store for a long time and direct stretching will damage the device.
[0068] Embodiment 4:
[0069] 1. Clean the transparent glass substrate with a surface roughness less than 1nm, and then heat dry it in a constant temperature oven for more than 6 hours;
[0070] 2. Apply a layer of detergent on the glass substrate, pour the PU on the glass substrate coated with detergent, vibrate slightly, spread the solution flat, and place it in a vacuum drying oven for drying (30°C, 24h). After drying, use a blade to carefully peel the flexible substrate from the glass substrate;
[0071] 3. Vacuum degree is 1×10 -4 Under Pa conditions, gold electrodes (80 nm) were evaporated on the PU substrate;
[0072] 4. Clean the microscope slides with a surface roughness of less than 1 nm and heat dry them in a constant temperature oven for more than 6 hours after cleaning;
[0073] 5. Spin-coat the prepared PVA solution onto a microscope slide (3000 rpm, 60 s), and dry the slide after spin coating (110°C, 1 min) to obtain a PVA sacrificial layer;
[0074] 6. A mixed chloroform solution of the prepared PS-PEO-PS triblock polymer, P3HT organic semiconductor and DA crosslinker (mass ratio PS-PEO-PS: P3HT: DA: chloroform = 3:25:1:200, 5000 rpm, 60 s, 80 nm) was spin-coated onto the PVA sacrificial layer, and then placed under 365 nm ultraviolet light for photolithography to form a crosslinked organic semiconductor layer;
[0075] 7. Observe the P3HT film under SEM and find that the surface of the P3HT film has evenly distributed pores. Figure 2 The porous semiconductor film 11 is shown;
[0076] 8. Place the spin-coated glass slide in a culture dish filled with deionized water, and place the culture dish on a hot plate (40°C) to dissolve the PVA sacrificial layer in the deionized water to obtain a semiconductor active layer. Transfer a layer of the semiconductor active layer to the flexible substrate and blow dry with nitrogen;
[0077] 9. Drip electrolyte on the semiconductor channel and insert Ag / AgCl gate electrode;
[0078] 10. Under test conditions: leakage voltage (V D )=-0.5V, gate voltage (V G ) scanning interval is 0.1~-1V, [EMIM][TFSI] ionic liquid is dripped on the semiconductor channel, and the on-off ratio (I on / I off )=2.1×10 3 , transconductance (gm )=0.59mS. If the device is not packaged, it is not easy to store for a long time and direct stretching will damage the device.
[0079] Embodiment 5:
[0080] 1. Clean the transparent glass substrate with a surface roughness less than 1nm, and then heat dry it in a constant temperature oven for more than 6 hours;
[0081] 2. Apply a layer of detergent on the glass substrate, pour the PU on the glass substrate coated with detergent, vibrate slightly, spread the solution flat, and place it in a vacuum drying oven for drying (30°C, 24h). After drying, use a blade to carefully peel the flexible substrate from the glass substrate;
[0082] 3. Vacuum degree is 1×10 -4 Under Pa conditions, gold electrodes (80 nm) were evaporated on the PU substrate;
[0083] 4. Clean the microscope slides with a surface roughness of less than 1 nm and heat dry them in a constant temperature oven for more than 6 hours after cleaning;
[0084] 5. Spin-coat the prepared PVA solution onto a microscope slide (3000 rpm, 60 s), and dry the slide after spin coating (110°C, 1 min) to obtain a PVA sacrificial layer;
[0085] 6. A mixed chloroform solution of the prepared PS-PEO-PS triblock polymer, P3HT organic semiconductor and DA crosslinker (mass ratio PS-PEO-PS: P3HT: DA: chloroform = 3:20:1:200, 5000 rpm, 60 s, 80 nm) was spin-coated onto the PVA sacrificial layer, and then placed under 365 nm ultraviolet light for photolithography to form a crosslinked organic semiconductor layer;
[0086] 7. Observe the P3HT film under SEM and find that the surface of the P3HT film has evenly distributed pores. Figure 2 The porous semiconductor film 11 is shown;
[0087] 8. Place the spin-coated glass slide in a culture dish filled with deionized water, and place the culture dish on a hot stage (40°C) to dissolve the PVA sacrificial layer in the deionized water to obtain a semiconductor active layer. Transfer one layer of the semiconductor active layer to the flexible substrate and blow it dry with nitrogen. Repeat the transfer of the second porous semiconductor layer to the first porous semiconductor layer and blow it dry with nitrogen.
[0088] 9. Drip electrolyte on the semiconductor channel and insert Ag / AgCl gate electrode;
[0089] 10. Under test conditions: leakage voltage (V D)=-0.5V, gate voltage (V G ) scanning interval is 0.1~-1V, [EMIM][TFSI] ionic liquid is dripped on the semiconductor channel, and the on-off ratio (I on / I off )=1.5×10 3 , transconductance (g m )=1.64mS. If the device is not packaged, it is not easy to store for a long time and direct stretching will damage the device.
[0090] Embodiment 6:
[0091] 1. Clean the transparent glass substrate with a surface roughness less than 1nm, and then heat dry it in a constant temperature oven for more than 6 hours;
[0092] 2. Apply a layer of detergent on the glass substrate, pour the PU on the glass substrate coated with detergent, vibrate slightly, spread the solution flat, and place it in a vacuum drying oven for drying (30°C, 24h). After drying, use a blade to carefully peel the flexible substrate from the glass substrate;
[0093] 3. Vacuum degree is 1×10 -4 Under Pa conditions, gold electrodes (80 nm) were evaporated on the PU substrate;
[0094] 4. Clean the microscope slides with a surface roughness of less than 1 nm and heat dry them in a constant temperature oven for more than 6 hours after cleaning;
[0095] 5. Spin-coat the prepared PVA solution onto a microscope slide (3000 rpm, 60 s), and dry the slide after spin coating (110°C, 1 min) to obtain a PVA sacrificial layer;
[0096] 6. A mixed chloroform solution of the prepared PS-PEO-PS triblock polymer, P3HT organic semiconductor and DA crosslinker (mass ratio PS-PEO-PS: P3HT: DA: chloroform = 3:20:1:200, 5000 rpm, 60 s, 80 nm) was spin-coated onto the PVA sacrificial layer, and then placed under 365 nm ultraviolet light for photolithography to form a crosslinked organic semiconductor layer;
[0097] 7. Observe the P3HT film under SEM and find that the surface of the P3HT film has evenly distributed pores. Figure 2 The porous semiconductor film 11 is shown;
[0098] 8. Place the spin-coated glass slide in a culture dish filled with deionized water, place the culture dish on a hot stage (40° C.), dissolve the PVA sacrificial layer in the deionized water, obtain a semiconductor active layer, transfer one semiconductor active layer to the flexible substrate, and blow dry with nitrogen, repeatedly transfer the second porous semiconductor layer to the first porous semiconductor layer, and blow dry with nitrogen, repeatedly transfer the third porous semiconductor layer to the second porous semiconductor layer, and blow dry with nitrogen;
[0099] 9. Drip electrolyte on the semiconductor channel and insert Ag / AgCl gate electrode;
[0100] 10. Under test conditions: leakage voltage (V D )=-0.5V, gate voltage (V G ) scanning interval is 0.1~-1V, [EMIM][TFSI] ionic liquid is dripped on the semiconductor channel, and the on-off ratio (I on / I off )=0.7×10 3 , transconductance (g m )=2.57mS. If the device is not packaged, it is not easy to store it for a long time and direct stretching will damage the device.
[0101] 11. After the device was stretched to 30% for 300 times, the device film thickness transconductance (g m )=1.97mS, retaining 76.65% of the transconductance.
[0102] It can be seen from Examples 1-6 that a stretchable organic electrochemical transistor includes, from bottom to top, a flexible substrate layer 1, an electrode layer, a semiconductor layer 5 and an electrolyte layer 6; the electrodes include a source electrode 2, a drain electrode 3 and a gate electrode 4; a multilayer porous semiconductor layer 5 is arranged above the source electrode 2 and the drain electrode 3, and an ion gel electrolyte layer 6 is arranged below the gate electrode 4; the multilayer porous semiconductor layer 5 is made of a stretchable multilayer porous solid semiconductor film prepared by spin coating, photolithography, and water transfer printing.
[0103] The organic electrochemical transistors prepared by the method for preparing a stretchable organic electrochemical transistor with a multilayer porous semiconductor active layer (i.e., the organic electrochemical transistors prepared in Examples 2 to 6) have a transconductance g of 0.0400 W / m2 / cm2 compared to the untreated electrochemical transistor (i.e., the organic electrochemical transistor prepared in Example 1). m and its film thickness uniformity transconductance g m,n The mechanical flexibility and long-term stability of the overall device are enhanced. This is because the electrolyte dripped on the P3HT porous membrane penetrates into the Figure 2In the porous semiconductor film 11 shown, the three-dimensional microstructure of the multi-layer porous semiconductor layer is conducive to increasing the contact area between the electrolyte and the semiconductor. Under gate voltage modulation, the electrolyte ions are injected into the semiconductor layer more quickly to regulate the drain current. The stretchable electrochemical transistor not only has a certain mechanical strength, but is also physically, chemically and electrochemically stable, and can be used in the field of flexible electronics and bioelectronics.
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A stretchable organic electrochemical transistor, characterized in that: The invention comprises, from bottom to top, a flexible substrate layer (1), an electrode layer, a multilayer porous semiconductor layer (5), an electrolyte layer (6) and a gate electrode (4); the electrode layer comprises a source electrode (2) and a drain electrode (3); the multilayer porous semiconductor layer (5) is a thin film of a stretchable multilayer porous solid semiconductor prepared by spin coating, photolithography and water transfer printing, and the material of the multilayer porous semiconductor layer (5) is prepared by mixing a polymer, an organic semiconductor and a crosslinking agent; the polymer is polystyrene-b-polyethylene oxide-b-polystyrene, One of polystyrene-b-polymethyl methacrylate-b-polystyrene, polystyrene-b-polyethyl acrylate-b-polystyrene, poly-N-isopropylacrylamide-b-polyethylene oxide-b-poly-N-isopropylacrylamide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene); the organic semiconductor is one of P3HT, Pg2T-T, DPP-DTT; the crosslinking agent is at least one of a bis-nitrogen heterocyclic crosslinking agent and a bis-azide crosslinking agent.
2. A stretchable organic electrochemical transistor according to claim 1, characterized in that: The material of the flexible substrate layer (1) is at least one of SEBS, PDMS and PU.
3. A stretchable organic electrochemical transistor and a method for preparing the same according to claim 1, characterized in that: The electrode layer is made of gold, and the thickness of the electrode layer is in the range of 80-150 nm.
4. The stretchable organic electrochemical transistor according to claim 1, characterized in that: The film thickness of multilayer porous solid semiconductors ranges from 200 to 300 nm.
5. The stretchable organic electrochemical transistor according to claim 1, characterized in that: The material of the electrolyte layer (6) is a salt aqueous solution or an ionic liquid, the salt aqueous solution is one of NaCl, KCl and PBS, and the ionic liquid is one of [EMIM][TFSI], [EMIM][FSI], [EMIM][DCA], [BMIM][PF6] and [EMIM][BF4].
6. A method for preparing a stretchable organic electrochemical transistor, for preparing a stretchable organic electrochemical transistor as claimed in any one of claims 1 to 5, characterized in that: The preparation process includes the following steps: Step 1: Clean the transparent glass substrate, blow dry it with nitrogen or heat dry it in a constant temperature oven for more than 6 hours after cleaning; Step 2: pouring SEBS, PDMS or PU onto a glass substrate coated with detergent, and after the solution is spread evenly, placing it in a vacuum drying oven for drying to obtain a flexible substrate layer (1), and after drying, peeling the flexible substrate layer (1) from the glass substrate with a blade; Step 3: Vapor-depositing a gold electrode with a thickness of 80-150 nm on the flexible substrate layer (1); Step 4: Clean the microscope slide, blow dry with nitrogen or heat dry in a constant temperature oven for more than 6 hours after cleaning; Step 5: Spin-coat the prepared PVA solution onto a microscope slide, and dry the spin-coated substrate to obtain a PVA sacrificial layer; Step 6: Spin-coat the prepared mixed chloroform solution of polymer, organic semiconductor and cross-linking agent onto the PVA sacrificial layer, and then place it under 365nm ultraviolet light for photo-cross-linking and curing to form a cross-linked semiconductor layer; Step 7: Soak the cross-linked organic semiconductor layer / PVA / substrate after photo-cross-linking and curing in chloroform for 10 seconds to remove the uncross-linked part of the polymer to form pores, blow off the surface solvent with nitrogen gas, and then dry; Step 8: placing the cross-linked organic semiconductor layer / PVA / substrate in a culture dish filled with 40°C deionized water, dissolving the PVA sacrificial layer in the deionized water to obtain a single porous semiconductor layer, transferring the first porous semiconductor layer onto the flexible substrate layer (1), and drying it with nitrogen, repeatedly transferring the second porous semiconductor layer onto the first porous semiconductor layer, and drying it with nitrogen, and repeatedly transferring the third porous semiconductor layer onto the second porous semiconductor layer, and drying it with nitrogen; Step 9: Drip the electrolyte onto the semiconductor channel.
7. The method for preparing a stretchable organic electrochemical transistor according to claim 6, characterized in that: In step 2, the drying temperature is 30° C. and the drying time is at least 24 hours.
8. The method for preparing a stretchable organic electrochemical transistor according to claim 6, characterized in that: In step 5, the drying temperature is 110° C. and the drying time is at least 1 min.
9. The method for preparing a stretchable organic electrochemical transistor according to claim 6, characterized in that: The drying method adopts at least one of constant temperature hot plate heating, oven heating and hot air heating.
Citation Information
Patent Citations
Method for preparing organic field effect transistor dielectric layer by using plasma crosslinking technology
CN105280816A
All-solid-state organic electrochemical transistor and preparation method thereof
CN114583053A